Comorbidities and incidence of heart failure with preserved ejection fraction: a systematic review and meta-analysis of cohort studies - Li Huang; Ping Xu; Zhenzhen Li; Jirong Yue; Ning Ge; Linlong Li; Xuchao Peng (BMJ Open, 2025)
Objective To identify comorbidities associated with incident heart failure with preserved ejection fraction (HFpEF) and quantify their HRs for early risk stratification and prevention.Design PROSPERO-registered (CRD42024505533) systematic review and meta-analysis. Primary analysis prioritised unadjusted HRs; exploratory analysis incorporated adjusted HRs.Data sources Ovid MEDLINE, Embase and the Cochrane Central Register of Controlled Trials through 15 June 2025.Eligibility criteria for selecting studies Cohort studies of adults (≥18 years) without prior HF reporting HRs for incident HFpEF-associated comorbidities. Exclusions: non-English publications, reviews, non-clinical studies and studies without HR data.Data extraction and synthesis Two reviewers independently extracted data and assessed quality (Newcastle-Ottawa Scale). Random-effects models pooled HRs. Heterogeneity was investigated using Galbraith/Baujat plots, meta-regression and subgroup analyses. Publication bias assessed via funnel plots, Egger’s and Begg’s tests.Results Among 61 eligible studies, 22 reporting unadjusted HRs formed the primary analysis, identifying five comorbidities with significant incident HFpEF risk: atrial fibrillation (AF) (HR 2.92, 95% CI 1.94 to 4.37, I²=86.6%), hypertension (HR 2.28, 95% CI 1.35 to 3.84, I²=96.9%), diabetes (HR 1.88, 95% CI 1.54 to 2.30, I²=58.2%), obesity (HR 1.70, 95% CI 1.45 to 2.00, I²=69.7%) and myocardial infarction (MI) (HR 1.62, 95% CI 1.18 to 2.23, I²=72.1%). Conversely, chronic kidney disease (CKD) (HR 1.44, 95% CI 0.68 to 3.06, I²=86.6%) and cerebrovascular disease (HR 1.72, 95% CI 0.93 to 3.18, I²=77.2%) showed non-significant associations. Exploratory analysis integrating unadjusted HRs from primary studies and adjusted HRs from 39 additional studies confirmed these five comorbidities as significant risk factors, with CKD again demonstrating non-significant association.Conclusion AF, hypertension, diabetes, obesity and MI constitute evidence-based targets for HFpEF risk stratification and preventive management. The CKD-HFpEF association requires validation in larger cohorts.PROSPERO registration number CRD42024505533.